Toxin profile and relative toxicity of three paralytic shellfish poisoning toxin- producing dinoflagellates from Malaysia - Usup, G.; Cheah, MY; Ng, BK; Leaw, CP; Ahmad, A. (Malaysian applied biology, 2006)
This study was carried out to determine the toxin profile and toxin content of Alexandrium minutum, Alexandrium tamiyavanichii and Pyrodinium bahamense var. compressum. These are three of the paralytic shellfish poisoning (PSP) toxin-producing marine dinoflagellates present in Malaysian waters. PSP toxins were analysed using an isocratic, post-column derivatization HPLC method with fluorescence detection. The three species differed significantly in toxin profile. A. minutum contained only GTX1, GTX2, ...